Fc-engineering significantly improves the recruitment of immune effector cells by anti-ICAM-1 antibody MSH-TP15 for myeloma therapy - Katja Klausz; Michael Cieker; Christian Kellner; Thies Rösner; Anna Otte; Steffen Krohn; Anja Lux; Falk Nimmerjahn; Thomas Valerius; Martin Gramatzki; Matthias Peipp (Haematologica, 2020)
Despite several therapeutic advances, patients with multiple myeloma (MM) require additional treatment options since no curative therapy exists yet. In search of a novel therapeutic antibody, we previously applied phage display with myeloma cell screening and developed TP15, a scFv targeting intercellular adhesion molecule 1 (ICAM-1/CD54). To more precisely evaluate the antibody's modes of action, fully human IgG1 antibody variants were generated bearing wild-type (MSH-TP15) or mutated Fc to either enhance (MSH-TP15 Fc-eng.) or prevent (MSH-TP15 Fc k.o.) Fc gamma receptor binding. Especially MSH-TP15 Fc-eng. induced potent antibody-dependent cell-mediated cytotoxicity (ADCC) against malignant plasma cells by efficiently recruiting NK cells and engaged macrophages for antibody-dependent cellular phagocytosis (ADCP) of tumor cells. Binding studies with truncated ICAM-1 demonstrated MSH-TP15 binding to ICAM-1 domain 1-2. Importantly, MSH-TP15 and MSH-TP15 Fc-eng. both prevented myeloma cell engraftment and significantly prolonged survival of mice in an intraperitoneal xenograft model. In the subcutaneous model MSH-TP15 Fc-eng. was superior to MSH-TP15, whereas MSH-TP15 Fc k.o. was not effective in both models - reflecting the importance of Fc-dependent mechanisms of action also in vivo. The efficient recruitment of immune cells and the potent anti-tumor activity of the Fc-engineered MSH-TP15 antibody hold significant potential for myeloma immunotherapy.